METAPHORS IN THE LYRICS OF THE DANCE OF THE GREAT DESTROYER BY FEAST - Julianto, Haekal; Siddiq, Mohammad; Fasha, Julia (Journal of Language and Literature, 2024)
This study explores the use of literary techniques, particularly metaphors, in imaginative writing, with a focus on song lyrics. The research examines the metaphorical elements in the song lyrics of "Tarian Penghancur Raya" by Feast. Employing a qualitative approach with a descriptive method, data were collected through note-taking techniques. The data analysis utilized the directed content analysis method to identify the types of metaphors and their implications from a semantic perspective. The findings reveal four explicit (in praesentia) and implicit (in absentia) metaphors in the song "The Great Destroyer Dance". These metaphors were proportionately applied, creating a balance that enhances the song's auditory appeal while effectively conveying its embedded messages. The study concludes that the strategic use of explicit and implicit metaphors contributes to the song's ability to evoke imagination and deliver its thematic depth. This research highlights the significance of metaphorical elements in enriching literary works and their potential impact on listeners.